Genomic Imprinting in Turner Syndrome: Effects on Response to Growth Hormone and on Risk of Sensorineural Hearing Loss - Hamelin, Catherine E.; Anglin, Greg; Quigley, Charmian A.; Deal, Cheri L. (The journal of clinical endocrinology and metabolism, 2006)
Context: Evidence exists for X-linked parent-of-origin effects in Turner syndrome, because phenotypic and cognitive profiles differ between 45,Xmaternal and 45,Xpaternal individuals. Objective and Design: We evaluated the parent-of-origin effect of the intact X chromosome on spontaneous growth, GH-stimulated height gain, and frequency of sensorineural hearing loss in 54 subjects with Turner syndrome recruited from a Canadian randomized, controlled trial of GH supplementation to adult height. Methods and Results: Microsatellite analyses revealed that 72% of nonmosaic 45,X subjects retained an Xmaternal, whereas 86% of nonmosaic 46,X,i(Xq) subjects carried an intact Xpaternal. No significant differences were noted between Xmaternal and Xpaternal subjects for parents’ heights, birth weight and length, and height, age, or bone age at study entry. In all subjects, and in those with Xmaternal, baseline height sd score correlated with midparental height (all: r = 0.511, P < 0.001; Xmaternal: r = 0.535, P = 0.001) and with mother’s height (all: r = 0.510, P < 0.001; Xmaternal: r = 0.574, P < 0.001) but only weakly with father’s height (all: r = 0.334, P = 0.015; Xmaternal: r = 0.292, P = 0.094). Using a linear model including age and height at GH initiation, subjects with Xmaternal had a greater mean height gain than those with Xpaternal (sd score difference and 95% confidence interval for all karyotypes was +0.43 and 0.04–0.82, P = 0.030, and for 45,X was +0.64 and 0.06–1.21, P = 0.031); X-linked imprinting explained 36–53% of the GH response. After pure tone audiometry testing, Xmaternal subjects were also less likely (P = 0.040) to have sensorineural hearing loss than Xpaternal subjects. Conclusion: This study provides evidence of an X-linked imprinting effect on GH response and on sensorineural hearing loss in Turner syndrome and should fuel the search for candidate genes.